The good biology teacher and its practice in the voice of training teachers (Revista Contexto & Educação, 2023)
The teacher plays a fundamental role in the teaching-learning process; in which, multiple elements constitute the teaching practice. The objective of this research was to analyze the profile of a good teacher and the characteristics of a good Biology class, considering the conception of four teachers in pedagogical training. It is considered here the relevance of incorporating the knowledge made possible by the pedagogical training course to the knowledge of the bachelor’s in Biology. The methodological approach was based on a qualitative approach. The data were collected through open interviews, carried out with four teachers in the field of Biology and undergoing training in the course of Formação Pedagógica para Graduados não Licenciados, from the Instituto Federal Sul-rio-grandense, Campus Pelotas. Considering the dialogue with the teachers in training, it is concluded that a good teaching practice in Biology involves characteristics related to affectivity, mastery of content and methodological strategies. In addition, in this research, it was found that reflective practice is assumed as the pedagogical concept of teachers in training.